Oil and Gas Tower Metaphor in Bojonegoro's Creative Economy Facility - Serli Uswatun Chasanah; Mufidah; Joko Santoso (Kirana Publisher (KNPub), 2026)
Bojonegoro is widely known as an oil and gas producing region, marked by traditional drilling towers still standing in the Wonocolo area. This identity has not yet been developed into a city landmark supporting the local creative economy. This study formulates a concept for transforming the form and meaning of the oil and gas tower into a creative economy facility functioning as a visual icon for Bojonegoro. A descriptive qualitative approach was applied through a combined metaphor design method, merging the tower's concrete visual elements with the abstract values of productivity and communal spirit held by local miners. Data were gathered through field observation of the towers and five leading craft centers, literature review, precedent study, and visual documentation, then analyzed through element identification, abstraction, and design reinterpretation. Findings show that the tower's vertical form, cross-braced frame, and mechanical character can be translated into a landmark tower twenty to twenty-five meters tall with a frame-patterned facade, accommodating production, training, and marketing spaces for five featured crafts within a total floor area of about 4,950 square meters. The resulting concept, the Industrial Creative Tower, is expected to strengthen Bojonegoro's image while providing growth space for craft-based creative economy.